Revalorización de la cuenta propiedad, planta y equipo en el Cuerpo de Bombero del Cantón Vinces en el periodo 2022. - Figueroa León, Lisbeth Estefanía (2023)
The present case study is called “Revaluation of the Property, Plant and Equipment Account in the Fire Department of the Canton Vinces in the Period 2022” the application of IPSAS 17 of Property, Plant and Equipment was carried out, information was provided necessary to carry out the revaluation of fixed assets in said public institution. In order to carry out this case study, we used the interview research technique directed at the accountant. Through this interview, the necessary evidence was obtained, such as the technical evaluation report and its financial information, which revealed the non-revaluation of the assets of the aforementioned institution, which is directly intertwined with the financial information. The revaluation of assets is very important since it allows us to know the current value of the institution's fixed assets, it is essential for the financial information of the company, in addition, it helps us to have credibility of the assets of said institution, it also helps us to know if we should continue to conserve our asset, said revaluation shows the book value in the Property, Plant and Equipment account, and thus we are executing what the regulations of the Ministry of Economy and Finance and IPSAS 17 indicate to us. Through this case study it was possible to confirm the importance of carrying out a revaluation in the Property, Plant and Equipment (Vehicle) account in the Vinces Canton Fire Department.